Persistence of Listeria monocytogenes in food commodities: foodborne pathogenesis, virulence factors, and implications for public health - Ranasinghe, R.A.S.S.; Satharasinghe, Dilan A.; Tang, ‪John Yew Huat; Rukayadi, Yaya; Radu, K.R.; New, C.Y.; Radu, Son; Premarathne, J.M.K.J.K. (Rynnye Lyan Resources, 2021)
Listeria monocytogenes is a ubiquitous pathogen found commonly in vast environment conditions and most commonly found in fresh-cut salads, raw fruits raw vegetables, sausages, cured meat, shellfish, refrigerated ready to eat food, soft cheeses, raw and under pasteurized milk. L. monocytogenes is a member of genus Listeria, along with five other members, such as L. innocua, L. ivanovii, L. seeligeri, L. grayi and L. murrayi. However, L. monocytogenes is the widely known species found in human cases, although a few cases with L. ivanovii have also reported. The infection caused by L. monocytogenes is known as listeriosis, and most affected populations are neonates, pregnant women, immune-suppressed and older people. Listeriosis is a severe condition with a higher level of hospitalization (94%) and around 16% fatality. Listeria can tolerate wide ranges of temperature, pH values, ions including Chlorides and Nitrites, different Oxygen levels. Therefore, L. monocytogenes is widely identified and survived easily on harsh environmental conditions. The ability of biofilm formation makes Listeria even harder to eliminate through food processing and associated surfaces. Although outbreaks are not very common, several large outbreaks have been documented in the literature. The extensive incubation period of this pathogen makes it challenging to identify the cause in most of the outbreaks, and most of the Listeria associated cases found to be sporadic. L. monocytogenes can cause substantial economic and public health impacts due to its effect on humans. Once contaminated, Listeria is hard to eliminate due to widespread presence in the environment, intrinsic physiological resistance, ability to adapt to external stresses, and the ability to grow at a wide range of temperatures. The objective of this review was to understand foodborne Listeria infections in humans and animals, the occurrence of infections and outbreaks, the growth and survival of L. monocytogenes in food-related industries, and risk reduction strategies.